2020
DOI: 10.1101/2020.08.26.265892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in structure and hibernation mechanism highlight diversification of the microsporidian ribosome

Abstract: Assembling and powering ribosomes are energy-intensive processes requiring fine-tuned cellular control mechanisms. In organisms operating under strict nutrient limitations, such as pathogenic microsporidia, conservation of energy via ribosomal hibernation and recycling is critical. The mechanisms by which hibernation is achieved in microsporidia, however, remain poorly understood. Here, we present the cryo-EM structure of the ribosome from Paranosema locustae spores, bound by the conserved eukaryotic hibernati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 48 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…We then used the cryo-EM maps to build the model of rRNA and ribosomal proteins. We found that, compared to the previously determined structures of V. necatrix and P. locustae ribosomes (both structures represent the same family of Nosematidae microsporidians and are very similar to each other) 31,32 , E. cuniculi ribosomes underwent further degeneration of numerous rRNA and proteins segments (Figs. S3-S6).…”
Section: E Cuniculi Ribosome Is the Smallest Eukaryotic Cytoplasmic Ribosome To Be Structurally Characterizedmentioning
confidence: 57%
See 4 more Smart Citations
“…We then used the cryo-EM maps to build the model of rRNA and ribosomal proteins. We found that, compared to the previously determined structures of V. necatrix and P. locustae ribosomes (both structures represent the same family of Nosematidae microsporidians and are very similar to each other) 31,32 , E. cuniculi ribosomes underwent further degeneration of numerous rRNA and proteins segments (Figs. S3-S6).…”
Section: E Cuniculi Ribosome Is the Smallest Eukaryotic Cytoplasmic Ribosome To Be Structurally Characterizedmentioning
confidence: 57%
“…3B). Notably, we found that most of these bulges are also lost in the previously determined structures of V. necatrix and P. locustae ribosomes, which was overlooked by previous structural analyses 31,32 .…”
Section: Microsporidian Rrna Is Stripped Of Highly Conserved Bulgesmentioning
confidence: 60%
See 3 more Smart Citations